KALIMAT IMPERATIF DAN PERSUASIF PADA CERAMAH MOTION GRAPHICS USTAD MUHAMMAD NUZUL ZIKRI: KAJIAN PRAGMATIK - Ghina Auliya Fitriyah; Burhanuddin; Ahmad Sirulhaq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study entitled Imperative and Persuasive Sentences in the Motion Graphics Lecture by The Scholar Muhammad Nuzul Zikri: A Pragmatic Analysis. The aim of this study is to describe forms of sentences (imperative or persuasive) and to grasp the pragmatic purposes of each sentence. This study employs a qualitative research design and a descriptive method. The observation method was used to collect data. To analyze data, this study used the intralingual matching method and the extra-lingual matching method. Moreover, to present the results, this study used the informal method. Furthermore, this method will contain forms of imperative sentences, such as: commands, requests, recommendations, prohibitions, and invitations. And form of imperative sentences such as: sentences expressing requests, advice, invitations, or prohibitions. Lastly, each of the sentence forms will be given its meaning, described in depth.